Structural Characterization of Mullite Formed from Heated Kaolin of Tamazert deposit (Algeria) - Zibouche, F.; Kerdjoudj, H.; Abadlia Mohamed, Taher (Asian Journal of Chemistry, 2011)
A quantitative analysis of the mullite phase obtained after sintering of the kaolin has been performed by treatment of X ray diagrams. Kaolin is treated in the range of 950-1400 ºC. The oxide NiO is added as internal standard after cooling to sintered sample kaolin. Bragg Brentano diffractometer, scanning electron microscopy and differential thermal analysis were used. Analyses of selected directions profile of mullite were carried out by using the adjustment of program, available in the software Highscore of Pan Analytical. The mullite phase that formed from kaolin appears at 1000 ºC, observed by XRD and tallies with DTA. The primary mullite crystal showed a plate-like morphology. Two kinds of morphology corresponding to primary (elongated grains) and secondary (equiaxed grains) mullite were observed. A bimodal crystallite size distribution was detected through XRD microstructural analysis from 1300 ºC. The apparent sizes obtained of crystallites are determined for mullite with directions-dependent (anisotropy).